(untitled) (Anais do Salão Inovação, Ensino, Pesquisa e Extensão, 2020)
Cardiovascular diseases (CVD) are known as the most leading cause of death in developed and developing countries. Atherosclerosis is characterized by total cholesterol and triglycerides deposition on the inner lining of blood vessels, resulting in plaque formation and eventually cause thickening and narrowing of the arteries Chia oil has the highest recognized α-linolenic acid (ALA) content. ALA is associated with beneficial changes in plasma lipids and the prevention of CVD. The aim of this study was to investigate the effects of chia oil supplementation on thickness measurements of the aorta in hyperlipidemic rats induced by high-fat diet. 24 male rats were divided into 4 groups, each containing 6 animals. Group 1 received a normolipid diet (NMD) and the other groups received the hyperlipid diet (HFD) during 90 days. After this period, the animals were supplemented daily for 30 days as follows: Group 1 (NMD) and Group 2 (HFD): 2 mL/kg body weight saline; Group 3 (HFD+SIM): oral simvastatin suspension at 10 mg/kg body weight; Group 4 (HFD+CHI): 2 mL/kg body weight of chia oil. After 30 days of supplementation, the animals were anesthetized the aorta was cut at the origin and removed from the heart. The entire aortas were dissected and tissue samples (5 mm) fixed by immersion at room temperature in a 10% formalin solution for 72 hours. Histological sections were obtained on a microtome and placed in a digital histological bath to shape the cut on the slide. The samples were then stained with hematoxylin-eosin (H&E). Images were made from photographs taken with a 10-MP camera attached to a LEICA® DM500 optical microscope. The aortic diameter measurements were made using LAS EZ-V 3.4.0 software. This study was approved by the Ethics Committee on Animal Use Experimentation of the Federal University of Pampa, CEUA, Uruguaiana, Rio Grande do Sul, Brazil (Protocol 042/2015). After 30 days of supplementation, thickness measurements of the aorta show a significant decrease (p